2017
DOI: 10.26480/msp.01.2017.39.41
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Ectoparasitic Fauna and Efficacy of Two Commercial Acaricides against Argus persicus in Layer Poultry

Abstract: Ectoparasites are responsible to transmit many bacterial and viral diseases in laying hens. A number of chemicals are used to manage tick infestation in laying birds. These include carbamates, avermectins, herbal products, pyrethroids and organophosphates and out of them pyrethriods are the most potent than all others. This study was designed to determine the prevalence of ectoparasitic fauna and to check the comparative ef�icacy of two different combinations of commercial acaricides in layer birds in all Tehs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, GRP78 has been found in the outer mitochondrial membrane in H460 cells after similar stress ( Shu et al, 2008 ). These observations indicate that the submitochondrial distribution of GRP78 depend highly on cell and stress type ( Sindhu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 92%
“…However, GRP78 has been found in the outer mitochondrial membrane in H460 cells after similar stress ( Shu et al, 2008 ). These observations indicate that the submitochondrial distribution of GRP78 depend highly on cell and stress type ( Sindhu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 92%
“…From the Table 2, compared with the blank group, the latent period and the number of shocks were significantly increased in the model group (P < 0.01). Reflecting the decline in memory of the perimenopausal model of mice (Sindhu et al, 2017). Compared with the model group, the GNA capsule group, SIS capsule group, high and mid dose group of TFR could significantly improve the incubation period of mice in avoid dark experiments and reduce the number of shocks (P < 0.01), improve mice memory.…”
Section: Resultsmentioning
confidence: 99%
“…According to the mathematical formula calculated at different ratio of total astragalosides and curcumin, the 3:7 group had highest evaluation score P, which indicated that group with the ratio of 3:7 had the best effect on improving the DM model. The efficacy the drug substance, mechanism of action, the clinical indications relatively clear, non-pharmacological effects of less interference, a variety of feedback mechanisms, targeted, efficacy is better than Pieces compatibility, quality control, suitable for industry promotion ( Sindhu et al, 2017 , Miao and Miao, 2012 , Deng and Huang, 2016 ). Astragalus for tonifying Qi and lifting yangqi to drug, turmeric is qi stagnation and blood stasis in a variety of pain syndrome.…”
Section: Discussionmentioning
confidence: 99%